2015
DOI: 10.1016/j.exger.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Breaking-up sedentary time is associated with impairment in activities of daily living

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Sardinha, L. B., Ekelund, U., dos Santos, L., Cyrino, E. S., Silva, A. M., Santos, D. (2015). AbstractIdentifying modifiable behaviours associated with prevention of activities of daily living (ADL) impairments is vital to implement preventive strategies for independent living in elderly. We aimed to examine the associations between objectively measured breaks in sedentary time with ADL impairments and physical independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
4
26
3
1
Order By: Relevance
“…Still, current results diverge from those observed among such studies of non-RA populations, in which sedentary behaviour (≤1.5 METs) and LPA (1.6–2.9 METS) are reported to be related to CVD risk profile and physical function [2224, 3640, 43, 46, 47, 64]. The absence of significant relationships in the current study, may therefore be due in part to the disproportionately higher levels of inflammation observed in RA, relative to other populations.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Still, current results diverge from those observed among such studies of non-RA populations, in which sedentary behaviour (≤1.5 METs) and LPA (1.6–2.9 METS) are reported to be related to CVD risk profile and physical function [2224, 3640, 43, 46, 47, 64]. The absence of significant relationships in the current study, may therefore be due in part to the disproportionately higher levels of inflammation observed in RA, relative to other populations.…”
Section: Discussioncontrasting
confidence: 97%
“…With regards to examination of the relationships between sedentary time, sedentary behaviour patterns and LPA with 1) individual CVD risk factors and 2) functional disability, the lack of significant associations reported herein are inconsistent with findings from extant research [2224, 3640, 43, 46, 47, 64]. Only the number of sedentary bouts/day  ≥ 20 min was significantly related to secondary outcomes (i.e., positive associations with fibrinogen and ESR).…”
Section: Discussioncontrasting
confidence: 94%
“…This information is clinically relevant to exercise professionals or surgeons who rehabilitate patients with intermittent claudication because it identifies patients who need more attention with interventions designed to reduce time spent in sedentary activities. Thus, in addition to stimulate increases in physical activity levels, it is also important to recommend breaks in the sedentary behavior, as it have been associated with lower functional impairment 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have identified an association between time spent sedentary and several important health outcomes that are particularly relevant to older adults, including functional impairments and reduced mobility [11]. In addition to the total time spent sedentary, the pattern of sedentary time may also be important, as more breaks in sedentary time have been associated with better physical function and cardiorespiratory fitness [12,13]. Therefore, simply breaking up sedentary time with short bouts of standing and light-intensity physical activity could be beneficial to health and function [14].…”
Section: Introductionmentioning
confidence: 99%